Optimalizace hydroenergetického využití VD Jesenice - Fajt, Mojmír (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Cílem této diplomové práce je návrh optimalizace využití hydroenergetického potenciálu vodního díla Jesenice. V rámci této práce byly zpracovány dvě návrhové varianty možného řešení malé vodní elektrárny, zahrnující hydraulické a hydrotechnické výpočty a výkresovou dokumentaci na úrovni studie proveditelnosti. V závěrečné části jsou shrnuty výsledky a uvedena doporučení pro další postup projektu malé vodní elektrárny Jesenice.

The objective of this thesis is a design of optimization of hydropower utilization for Jesenice reservoir. Two possible solutions of a new small hydroelectric power plant were presented in this thesis including hydraulic and hydrotechnical calculations and project documentation at level of feasibility study. The final part summarizes the results and gives the recommendations for the further project of the reconstruction of the small hydro power plant Jesenice.
Optimization of hydropower utilization of Jesenice reservoir
Keywords: Malá vodní elektrárna; turbína; hydroenergetika; Francis; Kaplan.; Small water plant; turbine; hydroenergetics; Francis; Kaplan.